Pulmonary function abnormalities in childhood cancer survivors treated with bleomycin. Issue 9 (2nd May 2014) - De, Aliva; Guryev, Igor; LaRiviere, Alejandro; Kato, Roberta; Wee, Choo Phei; Mascarenhas, Leo; Keens, Thomas G.; Venkatramani, Rajkumar
<x xml:space="preserve">Abstract</x> Background Bleomycin is associated with pulmonary toxic side effects including pneumonitis and pulmonary fibrosis. We evaluated the prevalence of long‐term pulmonary function abnormalities in children receiving bleomycin therapy in the context of current chemotherapeutic regimens. Methods A retrospective review of patients who received bleomycin between January 1999 and December 2011 was conducted. Abnormalities in the most recent pulmonary function test (PFT) at least 1 year after diagnosis were analyzed. Results Two‐hundred and seven patients had received bleomycin. The results of PFT performed at least 1 year from diagnosis were available for 80 patients. Median time of follow up was 3.9 years (range 1.1–11.76 years). Median cumulative dose of bleomycin was 65 IU/m2 (range 10–120). The most common diagnoses were Hodgkin lymphoma and germ cell tumor. At least one pulmonary function abnormality was present in 42 (52.5%) patients. When classified in groups, 22.5% patients had obstructive lung disease, 7.5% had restrictive lung disease, 28.8% had hyperinflation and 14% of patients had non‐uniform distribution of ventilation. Non‐Hispanic patients (OR 2.81) and children younger than 8 years (OR 4.14) had higher odds of having an abnormal PFT parameter. Very few patients had pulmonary symptoms. Conclusions More than half the patients who received bleomycin had subclinical pulmonary dysfunction as evidenced by abnormalities in pulmonary function tests, although the incidence of clinical symptoms was low. Pediatr Blood Cancer 2014;61:1679–1684. © 2014 Wiley Periodicals, Inc.